Prospective comparison of the digestive tract resistome and microbiota in cattle raised in grass-fed versus grain-fed production systems - Jiye Kwon; Windy Tanner; Yong Kong; Martina Wade; Chad Bitler; Marilia B. Chiavegato; Melinda M. Pettigrew (mSphere)
ABSTRACT Most antimicrobials sold in the United States are used in food animals. Farm management practices contribute to antibacterial resistance (AR). Controversially, grass-fed diets have been recommended over grain-fed diets to reduce AR in beef cattle. Ionophore feed additives (non-therapeutic antibiotics that enhance feed efficiency) may contribute to AR development. We used shotgun metagenomic sequencing of fecal swabs to prospectively compare the cattle gastrointestinal resistome and microbiota in two different production systems over five periods from pre-weaning to pre-harvest. Cattle were grass-fed and pasture-raised (system A, n = 33) or grain-fed with ionophore additives in feedlots (system B, n = 34). System A cattle averaged 639 lb and 22.8 months of age, and system B cattle averaged 1,173 lb and 12.4 months of age preharvest. In total, 367 antibiotic resistance genes (ARGs) and 329 bacterial species were identified. The resistome of system A cattle had higher alpha diversity than system B cattle over their lifespan (P = 0.008). Beta-diversity estimates indicated overlap in the pre-weaning resistome and microbiota in both systems, which diverged post-weaning, with increases in several medically important ARGs when system B cattle transitioned to a grain diet. Analysis of compositions of microbiomes with bias correction indicated that levels of tetracycline, macrolide, aminoglycoside, beta-lactam, and bacitracin ARGs were significantly higher in system B cattle pre-harvest. Resistome changes were highly correlated with bacterial community changes (Procrustes, M2 = 0.958; P = 0.001). Potentially modifiable farm management strategies, including diet and ionophores, may influence abundance and diversity of ARGs in fecal samples from cattle.IMPORTANCEAntibiotic resistance is a One Health threat. More antibiotics are used in agriculture than in human medicine. We compared the relative abundance of antibiotic resistance genes (ARGs) and bacterial species in cattle raised in two different cattle production systems (grass- and grain-fed). Fecal swab samples were collected at five time points spanning pre-weaning and prior to harvest. The antibiotic resistance gene and bacterial communities were relatively similar in the pre-weaning period when cattle in both systems were milking and on pasture. Resistance genes and bacterial communities diverged post-weaning when system B cattle were given a grain diet with feed additives for growth promotion containing non-medically important antibiotics (i.e., ionophores). The levels of medically important ARGs (e.g., macrolides) increased in system B grain-fed cattle post-weaning and were higher than in system A just prior to slaughter. These data provide additional evidence that farm management strategies impact the level of antibiotic resistance.